2015
DOI: 10.1038/nutd.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethnicity on glycaemic index: a systematic review and meta-analysis

Abstract: Objectives:Low glycaemic index (GI) foods are recommended to improve glycaemic control in diabetes; however, Health Canada considers that GI food labeling would be misleading and unhelpful, in part, because selected studies suggest that GI values are inaccurate due to an effect of ethnicity. Therefore, we conducted a systematic review and meta-analysis to compare the GI of foods when measured in Caucasians versus non-Caucasians.Methods:We searched MEDLINE, EMBASE and Cochrane databases for relevant articles. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Several Asian studies have demonstrated that LM50 is better in reducing blood glucose excursions than low mixtures, as observed in the present study. It is known that East Asian diets usually contain more carbohydrates, which have a higher glycemic index; therefore, LM50 may be more beneficial to patients with bigger blood glucose excursions than LM25 in Chinese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several Asian studies have demonstrated that LM50 is better in reducing blood glucose excursions than low mixtures, as observed in the present study. It is known that East Asian diets usually contain more carbohydrates, which have a higher glycemic index; therefore, LM50 may be more beneficial to patients with bigger blood glucose excursions than LM25 in Chinese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Within each domain, the investigators answered one or more signalling questions and these answers led to judgements of “low risk of bias”, “some concerns”, or “high risk of bias” [ 10 , 15 ]. Study methodology quality was assessed for each trial comparison based on eleven predetermined criteria outlined in Supplementary Table 2 which was adapted from a previous study [ 11 , 16 ]. This assessment identified protocol components that have been established as significant determinants of the accuracy and precision of PPGR measurements [ 17 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the white ethnics, Chinese diabetics are more β cell deficiency-oriented [30,31]. Deficient firstphrase insulin secretion in early β cell dysfunction causes great postprandial hyperglycemia excursion [30] and Chinese carbohydrate-rich diet fuels the flame [32,33]. Epidemiology studies repeatedly verified this characteristic of the population's blood glucose pattern [1,21].…”
Section: Discussionmentioning
confidence: 97%